Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/ijerph18052739
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Infection, Risk Perception, Behaviour and Preventive Measures at Schools in Berlin, Germany, during the Early Post-Lockdown Phase: A Cross-Sectional Study

Abstract: Briefly before the first peak of the COVID-19 pandemic in Berlin, Germany, schools closed in mid-March 2020. Following re-opening, schools resumed operation at a reduced level for nine weeks. During this phase, we aimed at assessing, among students and teachers, infection status, symptoms, individual behaviour, and institutional infection prevention measures. Twenty-four primary and secondary school classes, randomly selected across Berlin, were examined. Oro-nasopharyngeal swabs and capillary blood samples we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 25 publications
3
33
1
1
Order By: Relevance
“…14,33,35 Although the seroprevalence differed among the three studies, authors reported comparable seroprevalence in groups of children not attending school (0.5% versus 1%, and 1.4% versus 2.7%, respectively, for children attending in-person, or staying at home), 14,33 and adults who did not have occupational contact with children or COVID-19-positive patients (7.7% for daycare staff and 5.5% for the comparator adult group, 35 suggesting that exceptional schooling did not boost SARS-CoV-2 spread in the analyzed settings). In line with these observations, low seroprevalence reported in three additional cross-sectional studies adds up to the indication that schools did not develop into silent hotspots for viral transmission during the first wave of the pandemic, 15,30,34 likely due to the successful implementation of extensive preventive measures. In this regard, it is noteworthy mentioning two studies reporting seroprevalence in students from a small city in north France and from a large community school in Santiago, Chile.…”
Section: Sars-cov-2 Seroprevalence In Educational Settings (Serosurveys)supporting
confidence: 55%
See 1 more Smart Citation
“…14,33,35 Although the seroprevalence differed among the three studies, authors reported comparable seroprevalence in groups of children not attending school (0.5% versus 1%, and 1.4% versus 2.7%, respectively, for children attending in-person, or staying at home), 14,33 and adults who did not have occupational contact with children or COVID-19-positive patients (7.7% for daycare staff and 5.5% for the comparator adult group, 35 suggesting that exceptional schooling did not boost SARS-CoV-2 spread in the analyzed settings). In line with these observations, low seroprevalence reported in three additional cross-sectional studies adds up to the indication that schools did not develop into silent hotspots for viral transmission during the first wave of the pandemic, 15,30,34 likely due to the successful implementation of extensive preventive measures. In this regard, it is noteworthy mentioning two studies reporting seroprevalence in students from a small city in north France and from a large community school in Santiago, Chile.…”
Section: Sars-cov-2 Seroprevalence In Educational Settings (Serosurveys)supporting
confidence: 55%
“…Fifteen studies reported SARS-CoV-2 point prevalence in a total of 112,131 subjects, [12][13][14][15][16][17][18][19][20][21][22][23][30][31][32] including one study providing data collected during two rounds of testing within the COVID-19 Schools Infection Survey. 23 A total of 326 coronavirus infections were detected.…”
Section: Sars-cov-2 Positivity Rates In Educational Settings (Screening Studies)mentioning
confidence: 99%
“…So far, only a few studies have investigated teachers' fears of contracting SARS-CoV-2. A cross-sectional study in summer 2020 in Berlin, Germany revealed that about half of the school staff showed a medium to a very strong fear of infection, and 59% reported a moderate to a very high perceived risk of infection [13]. However, this study comprised only 112 teachers at 24 schools in Berlin, mirroring only a limited number of teachers' opinions, which can largely depend on their respective schools.…”
Section: Discussionmentioning
confidence: 92%
“…This was a cross-sectional analysis of a longitudinal study among students and school staff, including teachers, educators and facility staff, from 24 schools in Berlin (one class per school) and related household members. A first round of examinations of the same students and school staff had taken place in June 2020 [14]. The present second round was conducted between 2 and 16 November 2020.…”
Section: Study Design Setting and Participantsmentioning
confidence: 99%